A decade of experience with rotavirus vaccination in the United States - vaccine uptake, effectiveness, and impact - Pindyck, Talia; Tate, Jacqueline E; Parashar, Umesh D (Expert review of vaccines, 2018)
Prior to 2006, nearly every U.S. child was infected with rotavirus by 5 years of age, and rotavirus was the leading cause of severe childhood gastroenteritis. In February 2006 and June 2008, the Advisory Committee on Immunization Practices recommended a live attenuated pentavalent rotavirus vaccine (RV5) and a monovalent rotavirus vaccine (RV1), respectively, for routine vaccination of infants in the United States. We reviewed U.S. data on coverage, vaccine effectiveness (VE), and vaccine impact from 2006 to 2017. National rotavirus vaccine coverage estimates increased since vaccine introduction but plateaued at 71-75% in 2013-2015, a level 15-20% lower than that of other routine childhood vaccines. Pooled VE of full series RV5 and RV1 against rotavirus-associated hospitalizations and emergency department visits were 84% (95% CI: 80-87%) and 83% (95% CI: 72-89%), respectively. Vaccine introduction resulted in a median decline in rotavirus-associated hospitalizations and emergency department visits of 80% and 57%, respectively, along with indirect protection of unvaccinated age groups and a decrease in health-care costs. A biennial pattern in rotavirus detection emerged post-vaccine implementation. The increasing use of rotavirus vaccines has substantially diminished the burden and changed the epidemiology of rotavirus disease in U.S. children; efforts to increase rotavirus vaccine coverage should continue.